Phytochemical analysis of Indonesian gadung mango leaf (Mangifera indica L. var. gadung) and their antibacterial activity - ANI SULISTYARSI; TRI RAHAYU; CICILIA NOVI PRIMIANI; PUJIATI PUJIATI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sulistyarsi A, Rahayu T, Primiani CN, Pujiati. 2023. Phytochemical analysis of Indonesian gadung mango leaf (Mangifera indica L. var. gadung) and their antibacterial activity. Biodiversitas 24: 6295-6304. The study was carried out to find out the secondary metabolite compounds in mango leaf extract (Mangifera indica L. var. gadung) using qualitative, quantitative, LC-MS and antibacterial activity with well diffusion method in inhibiting the growth of Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922. Research used a quantitative approach of randomized block design with variations of concentrations of 60, 80, and 100%, K- (aquadest), and K+ (chloramphenicol) in three times repeated groups. The results of qualitative and quantitative phytochemical tests show that mango leaf extract contains flavonoids (63408.464 mg/kg), saponins 3212.942 mg/kg), tannins (1050.191 mg/kg), alkaloids (605.123 mg/kg) and steroid (1050.191 mg/kg). Test of flavonoid derivat extract using LC-MS shows apigenin, kaempferol, fisetin, catechins, quercetin, ramnetin, astragalin, hirsutrin, isocercitrin, hyperin, rhamnetin 3-glucoside, rhamnetin 3-o-?galactopyranoside, isorhamnetin 3-galactoside, amentoflavone, routine, hyperin-6-gallate, epigallocycin (4??8) epigallocycin-3-ogalate ester. Antibacterial testing on S. aureus forms an average clear zone diameter of 30.46, 31.43, 32.81 mm furthermor in E.coli is 23.23, 23.84, 24.23 mm. Data of clear zone diameter was analyzed using ANOVA two-way and showed a value of sg. 0,001<0,05. It can be concluded that Indonesian gadung mango leaf extract contains secondary metabolites which have the potential to be an antibacterial agent.